2014
DOI: 10.1002/bdra.23246
|View full text |Cite
|
Sign up to set email alerts
|

De novo 2q36.1q36.3 interstitial deletion involving the PAX3 and EPHA4 genes in a fetus with spina bifida and cleft palate

Abstract: The present study reinforces the hypothesis that PAX3 haploinsufficiency may be associated with neural tube defects in humans and suggests that the EPHA4 gene might be implicated during palate development. This report also illustrates the added value of array-CGH to detect cryptic chromosomal imbalances in malformed fetuses and to improve genetic counseling prenatally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Targeted homozygous disruption of EphA4 results in viable and fertile mice that exhibit defects in the corticospinal tract and hindlimb innervation as well as defects of the coronal suture (Dottori et al, ; Helmbacher et al, ; Ting et al, ). Of interest though, a recent report of a fetus with cleft palate and spina bifida that harbored a deletion of the genomic region including the EPHA4 and PAX3 genes suggested that EphA4 might be involved in palate development (Goumy et al, ). We, therefore, asked whether EphA3 might be redundant with EphA4 in the development of the secondary palate.…”
Section: Resultsmentioning
confidence: 99%
“…Targeted homozygous disruption of EphA4 results in viable and fertile mice that exhibit defects in the corticospinal tract and hindlimb innervation as well as defects of the coronal suture (Dottori et al, ; Helmbacher et al, ; Ting et al, ). Of interest though, a recent report of a fetus with cleft palate and spina bifida that harbored a deletion of the genomic region including the EPHA4 and PAX3 genes suggested that EphA4 might be involved in palate development (Goumy et al, ). We, therefore, asked whether EphA3 might be redundant with EphA4 in the development of the secondary palate.…”
Section: Resultsmentioning
confidence: 99%
“…The scenario in humans is somewhat similar in that there are 4 studies to date demonstrating the involvement of haploinsufficiency in the causation of spina bifida. The Pax3 gene and the EphA4 gene act in concert with each other in causing spina bifida due to interstitial deletion at position 2q36 [ 318 ]. Furthermore, in the same paper, Goumy et al [ 318 ] suggested that a similar phenomenon occurs in the mouse when taking into account the spina bifida phenotype seen on the Splotch mouse that is affected by both Pax3 [ 93 ] and EphA4 [ 319 ], albeit the link between the two in the mouse has yet to be ascertained.…”
Section: Haploinsufficiency In Mouse and Manmentioning
confidence: 99%
“…The Pax3 gene and the EphA4 gene act in concert with each other in causing spina bifida due to interstitial deletion at position 2q36 [ 318 ]. Furthermore, in the same paper, Goumy et al [ 318 ] suggested that a similar phenomenon occurs in the mouse when taking into account the spina bifida phenotype seen on the Splotch mouse that is affected by both Pax3 [ 93 ] and EphA4 [ 319 ], albeit the link between the two in the mouse has yet to be ascertained. The hedgehog pathway has also been implicated in humans, where spina bifida occurs when Patched is perturbed when implicated with Gorlin syndrome [ 320 ].…”
Section: Haploinsufficiency In Mouse and Manmentioning
confidence: 99%
“…It has been suggested that PAX3 haploinsufficiency may be associated with neural tube defects in humans but the precise mechanism is not elucidated while it is better characterized in animal models. 18,19 Among PAX3 heterozygotes often a specific variant is responsible for a very similar phenotype in particular concerning the presence or absence of limb involvement. In one of the families, the condition caused by a pathogenic variant in the paired domain of PAX3 p.Asn47Lys was first reported as a distinct syndrome of craniofacial, hand anomalies, and sensorineural deafness with very similar features in the mother and affected children.…”
Section: Discussionmentioning
confidence: 99%